Early Retirement and Financial Incentives: Differences Between High and Low Wage Earners - Rob Euwals; Elisabetta Trevisan (Institute for the Study of Labor (IZA), 2014)
This paper investigates the impact of financial incentives on early retirement behaviour for high and low wage earners. Using a stylized life-cycle model, we derive hypotheses on the behaviour of the two types. We use administrative data and employ a linear random effects model to test the predictions. We exploit exogenous variation in the replacement rate over birth cohorts of workers who are eligible to a transitional early retirement scheme. The empirical results show that low wage earners are, as predicted by the model, more sensitive to financial incentives. This implies that low wage earners will experience a stronger incentive to continue working in an early retirement scheme with a low implicit tax rate.
Keywords: J16; J22; J61; 330; pensions; early retirement; labour market behaviour